Position, status and role of Malay language in Malaysia - Alias, Nizamuddin; Shuaib, Farid Sufian (2014)
The position of Malay Language in Malaysia is provided by the Malaysian Federal Constitution. Due to the fact that the Malay Language has been sidelined during the colonial era, it took some time for the language to be put in its rightful position. The presence of various ethnicities who try to preserve their language; as well as the reluctance of the political elites in affirming the status of Malay language throws doubt to its future. Constitutional provisions and several laws relating to national language shall be examined to see whether the policies formulated have been in tandem with current laws. The paper concludes that the government should preserve the status quo as well as giving the national literary agency (Dewan Bahasa & Pustaka) enforcement powers in promoting the use of the national language.